Comparison of the efficiency of ultraviolet/ultrasonic (UV/US) and ultraviolet/zinc oxide (UV/ZnO) technologies as advanced oxidation processes in the removal of linear alkylbenzene sulfonate (LAS), an anionic detergent, from aqueous media - Tahereh Razavi (University of Brawijaya, 2021)
Surfactants are one of the most commonly found xenobiotics in municipal and industrial wastewater. The purpose of this study was to compare ultraviolet/ultrasonic (UV/US) and ultraviolet/zinc oxide (UV/ZnO) processes in the removal of LAS from aqueous media.In this study, a medium-pressure UV lamp (125 W), an ultrasonic device (400 W and 42 kHz), and ZnO nanoparticles (NPs) were used. The concentration of LAS was 0.5, 14, and 21 mg/L in all experiments. Contact time of 8, 16, and 24 minutes, pH of 3, 7, and 11, and NP concentrations of 50, 100, 150 mg/L were selected. Detergent extraction was performed using methylene blue active substances.The results showed that the efficiency of UV/US process in the removal of LAS was 89.35%, while the removal efficiency of UV/ZnO process was 81.27%. In both processes, the rate of detergent removal increased by elongating the contact time from 8 to 24 minutes. The efficiency of UV/US process in LAS removal was greater than that of the UV/ZnO process. The findings showed that the removal efficiency of UV/US process was directly correlated with pH, while it had an inverse correlation with the removal efficiency of UV/ZnO process.